Optimizing Precision Probiotics for Mitigating Graft-Versus-Host Disease - Nonyelum Ebigbo; Apple Long; Phinga Do; Laura Coughlin; Nicole Poulides; Talia Jewell; Shuheng Gan; Xiaowei Zhan; Andrew Y. Koh (Microorganisms)
Precision probiotics have shown great promise as novel therapies but have not been fully realized. One major obstacle is that different strains of the same gut microbiota species can induce markedly variable phenotypic outcomes. Here, we aimed to optimize and validate in a preclinical model, a six-species precision probiotic therapy for graft-versus-host disease (GVHD), an autoimmune complication following allogeneic stem cell transplantation. We had identified these six species as associated with protection against GVHD in a prior clinical study. We isolated strains of three of the targeted taxa (B. longum, C. bolteae, and Blautia spp.) from human stem cell transplant patients and characterized their SCFA production in vitro. We observed significant strain-to-strain variability among these gut microbiota taxa in their capacity to produce short-chain fatty acids, a microbiota-derived metabolite shown to be important for mitigating gut GVHD and inflammatory bowel disease, in vitro. We found that B. longum was able to augment butyrate production by C. bolteae and Blautia when co-cultured in vitro. “Optimized” precision probiotics mitigated GVHD and significantly increased survival (p = 0.013, log-rank test) in mice compared to a “standard” probiotic consortium of the same bacterial species obtained from a commercial repository. Importantly, the optimized probiotics resulted in significant increases in intestinal short-chain fatty acid concentrations compared to standard probiotics (p < 0.001, Mann–Whitney test). Our findings highlight the promising potential of utilizing an optimized precision probiotic approach to maximize therapeutic efficacy.